Antimicrobial susceptibility to polymyxin B and other comparators against Gram-negative bacteria isolated from bloodstream infections in China: Results from CARVIS-NET program - Xi, Jingyuan; Jia, Peiyao; Zhu, Ying; Yu, Wei; Zhang, Jingjia; Gao, Haotian; Kang, Wei; Zhang, Ge; Li, Jin; Wang, Tong; Xu, Yingchun; Yang, Qiwen (Frontiers in Microbiology, 2022)
Objective To investigate the bacterial distribution and antimicrobial resistance profile of clinical isolates from Gram-negative bacteria bloodstream infections (GNBSI) in China. Methods The clinical bacterial strains isolated from blood culture were collected during April 2019 to December 2021 in 21 member hospitals of China Bloodstream Gram-negative Pathogens Antimicrobial Resistance and Virulence Surveillance Network (CARVIS-NET). Antibiotic susceptibility test was conducted by broth microdilution method recommended by Clinical and Laboratory Standards Institute (CLSI, USA). WHONET 2021 and SPSS 22.0 were used to analyze data. Results During the study period, 1939 Gram-negative bacteria were collected from 21 hospitals, among which 1724 (88.9%) were Enterobacteriaceae, 207 (10.7%) were non-fermenting Gram-negative bacteria and 8 (0.4%) were others. The top five bacterial species were Escherichia coli (46.2%), Klebsiella pneumoniae (31.6%), Pseudomonas aeruginosa (4.9%), Acinetobacter baumannii (4.2%) and Enterobacter cloacae (3.0%). For K. pneumoniae, antibiotic resistance was mainly prevalent in hospital-associated bloodstream infections, while for A. baumannii, antibiotic resistance was mainly prevalent in community-associated bloodstream infections. It is worth mentioning that 94.1% of the 1939 Gram-negative isolates were susceptible to polymyxin B. The sensitivity of the strains involved in our investigation to polymyxin B is highly correlated with their sensitivity to colistin. Conclusions The surveillance results in CARVIS-NET-2021 showed that the main pathogens of GNBSI in China were Enterobacteriaceae, while E. coli was the most common pathogen. The resistance rates of K. Pneumonia, P. aeruginosa, A. baumannii and E. cloacae to multiple antibiotics kept on a high level. In many cases, polymyxin B and colistin has become the last-resort agents to combat bloodstream infections caused by multidrug-resistant (MDR) Gram-negative bacteria.